Research on the social capital, knowledge quality and product innovation performance of knowledge-intensive firms in China - Zhou, Xia; Min, Min; Zhang, Zhen (Frontiers in Psychology, 2022)
Given the importance of social capital for the success of knowledge-intensive firms (KIFs), scholars have investigated how social capital promotes product innovation through knowledge transfer. However, in contrast to the quantity of transferred knowledge, the role of knowledge quality has been largely ignored. Drawing on the knowledge-based view (KBV) of the firm, this study explores the influences of structural, relational, and cognitive social capital on product innovation and the mediating role of knowledge quality. A questionnaire-based survey was conducted from firm executives and core members of R&D department and data of 159 Chinese KIFs were obtained. Partial least squares-structural equation modeling was used for hypotheses testing. The results reveal that relational capital and cognitive capital have positive effects on product innovation performance, which are mediated by knowledge quality. However, the effect of structural social capital on knowledge quality is not significant. The results contribute to literature on firm innovation by examining how social capital indirectly affects product innovation performance through the quality of transferred knowledge. Moreover, the conclusions can help top management of KIFs to design more effective informal knowledge management approaches according to differentiated effects of three types of social capital on knowledge quality.